Discriminating disorder from difference using dynamic assessment with bilingual children. (February 2013) - Hasson, Natalie; Camilleri, Bernard; Jones, Caroline; Smith, Jodie; Dodd, Barbara
The DAPPLE (Dynamic Assessment of Preschoolers' Proficiency in Learning English) is currently being developed in response to a clinical need. Children exposed to English as an additional language may be referred to speech and language therapy because their proficiency in English is not the same as their monolingual peers. Some, but not all, of these children are likely to have a core language learning difficulty. Clinicians need to be able to distinguish disorder from difference due to a child's language learning context. The assessment used a test–teach–test format to examine children's ability to learn vocabulary, sentence structure and phonology. The assessment, which takes less than 60 minutes to administer, was given to 26 children who were bilingual: 12 currently on a speech and language therapy caseload and 14 children matched for age and socio-economic status who had never been referred to speech and language therapy. The DAPPLE data clearly discriminated the two groups. The caseload group required a greater amount of prompting to identify targeted words in the receptive vocabulary assessment and performed less well in the post-teaching expressive component. For sentence structure, the caseload group required more cues to acquire the targeted clause elements in the teaching phase. The caseload group made more phoneme errors at the initial and final assessments than the controls, and the type of errors made differed. Teaching resulted in greater positive change in percent phonemes correct for the caseload participants. Qualitative analyses of individual children's performance on the DAPPLE suggested that it has the potential to discriminate core language deficits from difference due to a bilingual language learning context. Future directions for development of the test are considered.